2021
DOI: 10.1186/s10033-021-00559-2
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Tire Forces Estimation of Multi-Axle Trucks Based on an Adaptive Treble Extend Kalman Filter

Abstract: Vertical tire forces are essential for vehicle modelling and dynamic control. However, an evaluation of the vertical tire forces on a multi-axle truck is difficult to accomplish. The current methods require a large amount of experimental data and many sensors owing to the wide variation of the parameters and the over-constraint. To simplify the design process and reduce the demand of the sensors, this paper presents a practical approach to estimating the vertical tire forces of a multi-axle truck for dynamic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Before optimizing the design, a mechanism analysis was performed first. Generally, radial tire forces are essential for vehicle modeling and dynamic control, so it is necessary to analyze the radial force of the tire in detail [28]. It can be seen that the load-bearing modes of non-pneumatic tires were bottom loading and top loading [29].…”
Section: Mechanism Analysis and Structural Designmentioning
confidence: 99%
“…Before optimizing the design, a mechanism analysis was performed first. Generally, radial tire forces are essential for vehicle modeling and dynamic control, so it is necessary to analyze the radial force of the tire in detail [28]. It can be seen that the load-bearing modes of non-pneumatic tires were bottom loading and top loading [29].…”
Section: Mechanism Analysis and Structural Designmentioning
confidence: 99%
“…This innovation, illustrated in Figure 1, effectively minimizes the impact of wave excitation on the main cabin by providing a mechanism for buffering and absorbing irregular wave forces. The vessel features two inflatable flexible pontoons made of PVC sandwich fabric, which resemble car tires [23]. These pontoons serve a dual purpose: firstly, they provide the necessary buoyancy for the entire vessel, akin to the supporting force exhibited by tires; secondly, they function as a vibration isolation and buffer mechanism.…”
Section: Structural Characteristics Of the Rescue Vesselmentioning
confidence: 99%
“…See Table 1. The vessel features two inflatable flexible pontoons made of PVC sandwich fabric, which resemble car tires [23]. These pontoons serve a dual purpose: firstly, they provide the necessary buoyancy for the entire vessel, akin to the supporting force exhibited by tires; secondly, they function as a vibration isolation and buffer mechanism.…”
Section: Structural Characteristics Of the Rescue Vesselmentioning
confidence: 99%
“…Zheng et al (2014), reported the Failure analysis of the Mining dump truck frame, considering the various path holes, obstacles, slope and curves on the bumpy road by combing the FEA, as well as static and dynamic testing [5]. Zhang et al (2021), reported a practical approach to estimating the vertical tire forces of a multi-axle truck for dynamic control. MATLAB/Simulink and Trucksim software are used, which can simulate a real truck used in the heavy vehicle industry [6].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2021), reported a practical approach to estimating the vertical tire forces of a multi-axle truck for dynamic control. MATLAB/Simulink and Trucksim software are used, which can simulate a real truck used in the heavy vehicle industry [6]. Guan et al (2018) reported the use of MSC ADAMS software for pavement design based on a multi-rigid-body dynamics model to calculate the force & displacements [7].…”
Section: Introductionmentioning
confidence: 99%